Pengaruh Kepemimpinan Kepala Sekolah terhadap Iklim Sekolah - Rini Aprilianda; Hanif Al Kadri (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
This study aims to analyze the effect of principal’s leadership on school climate. This study used quantitative methode. The population of this research was 81 teachers of SMK N 3 Padang. Sample were taken by using population sampling tecnique. The findings of this study had showed that: (1) the principal’s leadership was on middle range with score of 85.07%; (2) school climate on middle range with score of 77.54%; (3) the simple linear regression testing showed the effect of principal’s leadership on school climate was as follows: regression equation Y = 49,128 + 0,464X. The fact its significant value is smaller than 0.00 (0.000 < 0.05), it indicates that there is a significant influence of principal’s leadership on school climate, where R = 0,517 and R2 = 0,267. It’s recommended to analyse another independent variable effect on school climate.